DISHARMONISASI GUBERNUR DAN WAKIL GUBERNUR SUMATERA UTARA PERIODE 2008 – 2013 - Robert Antony Siregar; Yuwanto .; Susilo Utomo (Journal of Politic and Government Studies, 2016)
With regional autonomy the region of its increasingly dominant leadership in developing the potential of each area. The regional head and deputy as a command is selected in the leadership package in local elections expected to be more solid and harmonious. most areas in Indonesia disharmony between regional head and deputy. In an issue of North Sumatra governor and his deputy disharmony period 2008 - 2013, the local newspapers that intensively preach disharmony even featuring actor causes between 2 rumored strained. This study aims to determine how the process and chronologically through the concept of disharmony with aspects of assessment. By using descriptive analysis found that the disharmony of this stems from the recognition of Governor Syamsul Arifin about out of harmony with his deputy and then to the parliament so that a debate in the parliament of North Sumatra was later published by some local newspapers in North Sumatra. newspaper stories become the way in researching the disharmony. there are two major issues related to this disharmony that roles and responsibilities are problematic and the inauguration of the regional secretaries were impressed defenitif delay. In fact a package of proven leadership has elements that could potentially encourage disharmony. Of the various aspects of the assessment can be seen that the disharmony is happening not only political and legal aspects but personal and relational aspects as well as organizational and technical aspects of the delivery is no longer fit to raise a more solid leadership and harmony. Keep in consideration of the election of a package in which the position of deputy head of the region have an impact in improving the performance of regional heads. Another alternative is the deputy head of the region mainly been vice governor eliminated only through civil or even the removal of a package of election.